DISCOURSE ANALYSIS ON VAGUE LANGUAGE USED IN ADVERTISEMENT VIDEOS BY TIKTOK INFLUENCERS - Suarez, Aris Pet Angeli; Revamonte, Coreen Joy L.; Balimbingan, Muhadir H.; Irong, Isabella Angel C.; Suco, Eubien Jane V. (International Journal of Language and Literary Studies, 2023)
The study aimed to examine how vague language (VL) is employed by social media influencers in their TikTok video advertisements. This study used discourse analysis, specifically pragmatic analysis, which focuses on the meaning of a language within its social context. The corpora consisted of 25 transcribed texts from video advertisements of the five Filipino social media influencers. Results revealed that the selected influencers use VL in their TikTok video advertisements. Results further revealed that three strategies in the use of VL were identified: hedges, vague words and vague implication. Hedges include adapters, rounders, plausibility shields, and attribution shields. Influencers commonly use these strategies to create a more modest and credible image for the product or service they advertise and to avoid making explicit claims that could be challenged or refuted. Finally, it was found that the use of these strategies has contributed to the effectiveness of advertisements as evidenced in the engagement rate. Based on the results, the researchers recommend that social media advertisers should ensure that VL is used ethically and responsibly to avoid deception or misinformation and that there be further research on the use of VL in advertising across different social media platforms and languages.